1875 Mo. Laws 50-51 - (:unkn) unknown (My University, 1875)
An Act to prevent the carrying of weapons in public assemblies of the people, and to repeal "An Act to prevent the carrying of concealed weapons," approved March 26, 1874, § 1: Prohibited concealed carry of any fire-arms, Bowie-knife, dirk, dagger, slung-shot, or other deadly weapon in any church, place of religious worship, school-room, assembly for educational, literary, or social purpose, election precincts on election day, or court-room while court is in session, or into any other public assemblage of persons met for purposes other than militia drill or under militia law.
Keywords: SENSITIVE PLACES